154k views
3 votes
9(k-4)-7k=32-2(k-8)

User Durell
by
5.2k points

2 Answers

5 votes

Answer k=52

Explanation:

9k-36-7k=32-2k-16

combine like terms

2k-36=16-2k

move the -2k to the other side

k-36=16

than you do

36+16=52

Answer

k=52

User Enterx
by
6.1k points
6 votes

Answer: k=21

Explanation:

1. Distribute the 9 to the k and the -4 in the parentheses.

9 · k = 9k and 9 · -4 = -36

You now have 9k - 36 - 7k. You can combine the like terms of 9k and -7k and get 2k, giving you 2k - 36.

2. For the other side of the equation, you also distribute -2 to the k and -8 in the parantheses.

-2 · k = -2k and -2 · -8 = 16

You now have 32 - 2k + 16. Combine the like terms 32 and 16 (32 + 16) and you get 48. This gives you the equation 48 - 2k.

3. Now you should have the equation 2k - 36 = 48 - 2k.

You want the k on one side of the equation so you need to cancel out one of them. I cancelled out -2k by adding 2k to it. You also need to add this 2k to your 2k on the other side of the equation.

Ex: 2k - 36 = 48 - 2k

+2k +2k

4. Now you should have 4k - 36 = 48. You need to get 4k by itself so cancel out -36 from both sides by adding 36 to -36 and adding 36 to 48.

You should now have 4k = 84 (48 + 36 = 84).

Divide both sides by 4 to get k by itself. 4 divided by 4 makes k and 84 divided by 4 equals 21. This makes k = 21, which is your answer.

User Richard Cooke
by
5.8k points